Financial Contagion and Globalization: Evidence from South Asian Countries - Ullah, Muhammad Usman Sana; Haq, Naveed Ul; Laeeq, Hood; Raja, Ammar Aftab (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2018)
This study investigates the contagion and globalization between the South Asian (Pakistan, India, Bangladesh and Sri Lanka) and five largest economies (US, UK, China, Japan and Germany) stock markets. Daily stock returns data from 1st July 1997 to 30th June 2015 consisting of total 4695 observation is analyzed.Â DCC GARCH is applied to calculate the conditional correlation coefficients to overcome the issue of heteroscedasticity. Null hypothesis of no globalization got rejected eleven times out of twenty while the hypothesis of no contagion got rejected six times. Further analysis of conditional correlation coefficients confirmed the impact of 9/11 attacks, Subprime mortgage crises and Europeans debt crises on the Indian market. Impact of 9/11 attacks also found on Pakistani and Sri Lankan stock exchanges, while Dhaka stock exchange remained independent of all shocks. In sum, the South Asian stock markets remained isolated from the global shocks except India. Isolation of South Asian stock markets from the global shocks is due to their lower integration with the global markets. This study provides some useful recommendations to the investors and policy makers. Results suggests that Indian stock exchangeÂ getÂ contagion impact from the major economies, so authorities of India should have to take measure to decouple the market from the global shocks. The markets of Bangladesh, Sri Lanka and Pakistan are not properly integrated with global financial system, so the authorities of these countries should have to take proper steps to liberalize the markets. This paper presents the first empirical study on financial contagion and globalization of South Asian countries.